Óleo de semente de romã (Punica granatum L.) : métodos de extração e perfil de ácidos graxos - Santos, Jideane Menezes (2021)
The pomegranate (Punica granatum L.), considered one of the oldest fruits, belongs to the Lythraceae family and is originally from Asia. Its cultivation is widely spread in many tropical and subtropical countries. Its nutraceutical properties have attracted the attention of many researches, especially the oil obtained from seeds, a residue generated by the juice processing industries. Thus, this review aimed to discuss the content of fatty acids present in pomegranate seed oil as well as to provide an overview of the main extraction methods such as those involving the use of organic solvent, cold pressing, assisted by ultrasound and supercritical fluid. This study is a narrative review, whose research was carried out from scientific articles and academic works on the Capes Portal, in the Science Direct, PubMed and Scopus and Academic Google databases. Some descriptors were used, such as: “pomegranate seed oil” AND “extraction”, “pomegranate seed oil” AND “fatty acids” and “pomegranate seed oil”. The selection was made considering only works available in full and that had been published between the years 2011 to 2021. According to the evaluated studies, it was possible to verify the high content of punic acid, geometric and positional isomer of linolenic acid, which represented more than 80% of the total fatty acids in some works. According to the literature, extraction using organic solvents is disadvantageous in relation to some aspects such as thermal degradation, chemical and quality changes in the extracted oil and environmental problems. Techniques using supercritical fluid, ultrasonic waves and cold pressing are well evaluated in these aspects compared to the previous one.